Building the Dream: The future of Western Australia’s construction industry - Crowe, Adam; Duncan, Alan; Rowley, Steven (Bankwest Curtin Economics Centre, 2024)
Building the Dream, the ninth report in the BCEC Focus on Industry series, reveals that at current rates of dwelling completion, Western Australia will fall well short of the National Accord target of 25,000 new dwelling units per year.